2015
DOI: 10.5812/ijp.322
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects in Children and Adolescents With Major Thalassemia: A Case-Control Study

Abstract: Background: Thalassemia is an inherited blood disease. It is a serious public health problem throughout the Mediterranean region, the Middle East and the Indian subcontinent, as well as in Southeast Asia. Objectives: Thalassemia is an inherited blood disease. It is a serious public health problem. In this study we assessed psychological aspects in Iranian children and adolescents with thalassemia major. Patients and Methods:In this case-control study sixty healthy subjects aged 7-18 years and Sixty Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
10
0
5
Order By: Relevance
“…Changes in physical appearance also contribute to a bad self-image. Serious complications that can occur such as heart failure, arrhythmia, liver disorders, endocrine complications and infections (Behdani et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in physical appearance also contribute to a bad self-image. Serious complications that can occur such as heart failure, arrhythmia, liver disorders, endocrine complications and infections (Behdani et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the prevalence of depression in thalassemia patients internationally, ranging from 10% to 50%, but we could not find any publication from Saudi Arabia [ 7 , 8 , 13 ]. Different reports from Iran reported that depression in BTM patients is a predominant presentation ranging between 12% and 30% and that up to 54% of patients found to have a type of psychopathological disorder [ 14 - 17 ]. More serious psychological complications in BTM patients can present, as it was reported in a study conducted in Iran that up to 27.3% of patients considered suicide in the year before the study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Jain, Bagul, and Porwal (2013) revealed that psychosocial problems are more common in adolescents and young adults with thalassemia than in other age groups. Similarly, Behdani et al (2015) found that adolescents with thalassemia major have a lower quality of life than their healthy peers, as well as greater depression and behavioral problems. Further, research demonstrates that adolescents with thalassemia major have marked decreases in academic achievement which might be attributed to frequent absence from school for receiving a blood transfusion, hospital appointments and treatment of complications (Nashwan et al, 2018).…”
Section: Introductionmentioning
confidence: 94%